Epistimologi Fundamental Ekonomi - Khotimah, Husnul; Panisa, Panisa; Nasution, Silpiah Jahrah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Science dichotomy that separates science that is far from the values of religion and science that is concerned with the values of religion has given birth to Islamic economics. In epistemology of Islamic economics, means the economy will talk about the nature of Islam and its fundamentals. Islamic Economics examines the process of human activities related to the production, distribution and consumption in communities that implement the contract in fiqh mu'amalat. Islamic economics as a discipline clearly has epistemological foundations. Discussing economic epistemoligi Islam means examines the origins of Islamic economics, methodology and scientific validity. When talking about the Islamic economic epistemology, meaning the economy will talk about the nature of Islam and its fundamentals. Islamic epistemology based Islamic economics as it relates to the worldview of Islam itself